EL PARQUE DE DIVERSIONES COMO LABORATORIO DE FÍSICA MECÁNICA - XIOMARA MURILLO (Universidad Distrital Francisco José de Caldas, 2011)
This paper shows results using an amusement park premises, in order to improve appropriation of such physics concepts such as; circular motion, work and energy, among others. I assumed the park as an experimental lab. That's the reason why I performed and applied a guidance material, taking it as a learning object. These guides have the objective to relate theory and experience by the analysis about some mechanical attractions. The experiment was carried out with students in the subject "mechanical physic" in a public university, from Bogota, Colombia. I developed both, sessions in the classroom and in the amusement park, also was assessed on three times (before, during and after to the park visit). Analysis of results and conclusions, allow us to see the level of skills development, dimensions of knowledge and strengths of the process, showing an improvement about significance and construction on concepts discussed.